Preliminary CFD Study on the effect of fuel injector coking on fuel spray characteristics - Agarwal, Parash; Sethi, Vishal; Gauthier, Pierre Q.; Sun, Xiaoxiao; Liu, Yize (American Society of Mechanical Engineers (ASME), 2018)
Fuel injector coking involves deposit formation on the external or the internal surfaces of an injector or nozzle. This deposition of carbonaceous particles can result in uneven fuel-spray characteristics or localised burning (hot spots), which may eventually lead to mechanical failure or simply have a detrimental effect on the combustion system. This study focuses on the use of numerical methods to investigate the effect of coke formation on both the atomiser internal flow passages and its spray characteristics. Three different cases are examined; one investigating the clean injector; the second investigating the effect of internal coking; and the third investigating the effect of nozzle tip coking. A pressure swirl atomiser was considered for the purpose of the study. Validation of the numerical results for the clean injector condition is carried out against published experimental data. Two arbitrary geometries of coke deposits were created. The Volume of Fluid (VOF) multiphase model has been used in conjugation with a Geometrical Reconstruction Scheme (GRS) to simulate the interface representing the two phases. Spray cone angle and the liquid film thickness for the clean injector condition predicted by numerical simulation agreed well with the experimental data. Instabilities in the air core and the spray angle were also observed because of the presence of coke layers. Fouling present on the injector tip resulted in an earlier breakup of the film which can thereby affect the flame lift-off length. These stated observations can have significant implications both on the performance as well as the life of the combustion systems, thereby establishing the relevance of this study.